2018
DOI: 10.1101/487439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of the genetic background on gene deletion phenotypes inSaccharomyces cerevisiae

Abstract: Loss-of-function (LoF) mutations associated with disease don't manifest equally in different individuals, a phenomenon known as incomplete penetrance. The impact of the genetic background on incomplete penetrance remains poorly characterized. Here, we systematically assessed the changes in gene deletion phenotypes for 3,786 gene knockouts in four Saccharomyces cerevisiae strains and 38 conditions. We observed 16% to 42% of deletion phenotypes changing between pairs of strains with a small fraction conserved in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In yeast, for example, 80% of gene knock-outs are silent in the sense that they produce no phenotypic effect when the yeast is well-nourished (Hillenmeyer et al, 2008). That result has been broadly confirmed by Galardini et al (2018) who have shown the extent to which the effect of a gene deletion depends on the genetic background. They conclude that “interpretation of the impact of genetic variants on the phenotypes of individuals would likely need detailed gene-phenotype information in more genetic backgrounds than that of a model individual.” We would add that the phenotype background must also be relevant.…”
Section: Main Sectionssupporting
confidence: 55%
See 1 more Smart Citation
“…In yeast, for example, 80% of gene knock-outs are silent in the sense that they produce no phenotypic effect when the yeast is well-nourished (Hillenmeyer et al, 2008). That result has been broadly confirmed by Galardini et al (2018) who have shown the extent to which the effect of a gene deletion depends on the genetic background. They conclude that “interpretation of the impact of genetic variants on the phenotypes of individuals would likely need detailed gene-phenotype information in more genetic backgrounds than that of a model individual.” We would add that the phenotype background must also be relevant.…”
Section: Main Sectionssupporting
confidence: 55%
“…The boundary between regulatory networks and DNA is necessarily a two-way boundary. The regulatory networks can filter genetic changes, acting as what we have characterized as a “cloud” at the boundary (Noble and Noble, 2017; Galardini et al, 2018).…”
Section: Main Sectionsmentioning
confidence: 99%
“…Genetic background is known to play a significant role in the effect of a mutation. A large study in Saccharomyces cerevisiae recently found that 16% to 42% of deletion phenotypes changed between pairs of strains, depending on the environment (39). To fully probe the influence of the variants and genes that we identified in our screen, these variants need to be studied in the ST93 background.…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of those collections is that they rely solely on the genetic backgrounds of lab strains and as we discuss in this review; strains used in industrial process are not derivatives of lab strains. Recently, a study demonstrated this point by showing a high degree of genetic background dependency by analysing ~4,000 gene knockouts in four different strains background of the same species (Galardini et al, ).…”
Section: Leveraging Genome‐scale Diversity For Host Optimizationmentioning
confidence: 98%